Preventive role of cinnamaldehyde against tenuazonic acid- and Freund’s adjuvant-induced histopathological and biochemical alterations in the mouse model - Kumari, Ankita; Singh, Karuna (Frontiers in Microbiology, 2023)
Introduction This study was designed to assess the protective role of cinnamaldehyde (Cin) against the synergistic effect of tenuazonic acid (TeA) and Freund’s adjuvant on different organs of Swiss albino mice. Methods TeA was administered singly and in combination with Freund’s adjuvant intra-peritoneally. The mice were divided into control (vehicle treated), mycotoxicosis-induced (MI) groups, and treatment groups. The route of administration of TeA was intra-peritoneal. The treatment group (FAICT) received Cin orally as a protective agent against TeA-induced mycotoxicosis. The effects on performance, differential leukocyte counts (DLC), and pathological measurements in eight organs (liver, lungs, kidney, spleen, stomach, heart, brain, and testis) were taken into consideration. Results The body weight and feed consumption decreased significantly in the MI groups, which were reversed in the FAICT group. The necropsy observations revealed an increase in the relative organ-to-body weight percentage in the MI groups, which was restored to normal in the FAICT group. Freund’s adjuvant enhanced the effects of TeA on DLC. The antioxidant enzymes SOD and CAT decreased, while MDA increased in the MI groups. Caspase-3 activity was reduced in all organs and remained stable in the treatment group. TeA elevated the ALT concentration in the liver and kidneys and the AST in the liver, kidney, heart, and brain tissues. The oxidative stress induced by TeA in the MI groups was ameliorated in the treatment group. Histopathological observations consisted of NASH, pulmonary oedema and fibrosis, renal crystals and inflammation, splenic hyperplasia, gastric ulceration and cyst, cerebral axonopathy, testicular hyperplasia, and vacuolation in the MI groups. However, no such pathology was recorded in the treatment group. Discussions Thus, it can be concluded that the toxicity of TeA was found to be enhanced when combined with Freund’s adjuvant. However, Cin exhibited promising protective effects against TeA + Freund’s adjuvant toxicity and reverted the pathological alterations caused by them. Additionally, this study emphasizes Freund’s adjuvant’s ability to increase mycotoxicity rather than just acting as an immunopotentiator.